Gli effetti dello slackline training sulla postura corporea nei judoisti - Santos, L.; Fernandez-Rio, J.; Fernandez-Garcia, B.; Due Jakobsen, M. (Medicina dello Sport, 2014)
Aim. This study investigates the effects of Slackline on postural control and jumping performance in judoists. Methods. Fifteen judoists were randomly distributed into an experimental group (EG: N.=8, 16.0±1.73 years) and a control group (CG: N.=7, 15.43±2.23 years). While both groups followed the same judo training program during the 4 weeks of the study, the EG completed an additional supervised Slackline training (2 sessions per week of 60 min each one, for 4 weeks). Several key postural control parameters were assessed with a footscan baropodometric platform (sway length, ellipse surface and average speed) in three tests: bipedal support, right-foot support and leftfoot support. All these tests were developed during 10 seconds and in an open eyes situation. Additionally, jumping performance expressed as flight time, was assessed in two tests (the drop jump [DJ] and the countermovement jump [CMJ]) at baseline and after 4-week follow-up. Moreover, perceived exertion (RPE) was rated on a 6-20 Borg scale, and local muscle perceived exertion (L-RPE) was obtained after each training session. Results. Final tests showed that the EG significantly reduced bipedal sway length, bipedal average speed, right-foot sway length and left-foot sway length, and the CMJ flight time was increased (P<0.05). On his part, the average RPE score of all training sessions was 10.86±0.62, and the average of L-RPE of all training sessions were 30.71%, 20.53% and 18.74% for the calves, hamstrings and quadriceps respectively. Discussion. The results indicate that a 4-week supervised Slackline training program has a significant positive effect on young judoists` postural control and jumping performance. Conclusion. Slackline training can be safely incorporated into a judoists` training protocol to improve postural control and jumping performance.